2012
DOI: 10.17503/agrivita-2012-34-2-p105-114
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Fruit Quality in the Progenies of Day-Neutral and Short Day Hybrid Strawberry Cultivars

Abstract: This study was conducted to evaluate the heritability, heterosis, and correlation among firmness, total soluble solid (TSS), and color in the F 1 hybrids between two day-neutral (DN) and six short-day (SD) cultivars. The firmness of DN cultivars and the sweetness of SD cultivars were considered as a criterion in choosing parent cultivars. Parents and eleven F 1 progenies were grown in completely randomized block design. Heritability of TSS, color (a*: opponent channel between red/magenta and green), and firmne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…Pulp firmness did not correlate significantly with any other variables. This disagrees with the results found by Murti et al (2012), for which pulp firmness was significantly correlated with color of the epidermis and soluble solids content of the fruits.…”
Section: Genotypecontrasting
confidence: 99%
See 1 more Smart Citation
“…Pulp firmness did not correlate significantly with any other variables. This disagrees with the results found by Murti et al (2012), for which pulp firmness was significantly correlated with color of the epidermis and soluble solids content of the fruits.…”
Section: Genotypecontrasting
confidence: 99%
“…The fact that there was no difference between the genotypes studied for pulp firmness was contrary to the expected one, considering that there is a wide variability between different populations of strawberry for this characteristic (Hancock et al, 2008) and it is subject to high selection gain in breeding programs, and may reach more than 50% gain per selection (Murti et al, 2012).…”
Section: Average Commercial Fruit Weight (G Fruit -1 )** Genotypementioning
confidence: 73%
“…Whitaker et al 2012when studying 15 experimental hybrids and two parents ('Radiance' and 'Elyana') in two locations (Balm and Dover, in Florida) observed the heritability in the broad sense for Sh with low (h² = 0.18±0.03), for average fruit weight with medium to high (h² = 0.53±0.04) and for the other analyzed traits with a median value (h² = 0.30 to 0.41) supporting themedium to high heritability values of some traits in the present study. Murti et al (2012) reported that estimates of heritability (h²) for F 1 populations and 8 parents used as parents ('Akihime', 'Sachinoka', 'Keumhyang', 'Seolhyang', 'Maehyang', 'Soogyeong', 'DNKW001' and DNKW002 ') was 0.498 for fruit firmness and 0.678 for soluble solids content, in a study conducted at the National University of Gangneung-Wonju, Korea, values close to those found in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic base in the cultivated strawberry is relatively narrow (Sjulin and Dale, 1987); however, high levels of heterozygosity in the strawberry genome and the hybrid nature of F. •ananassa (Hancock, 1999;Maas, 1998) make breeding for disease resistance a viable option. Despite much knowledge on fusarium wilt diseases in other crops, little is known of the genetics of resistance in strawberry, where most inheritance studies on strawberry populations have been on fruit traits (Murti et al, 2012;Shaw and Sacks, 1995;Verma et al, 2003). From a study in Japan of Fof resistance in strawberry, Mori et al (2005) reported bimodal segregation of disease resistance to fusarium wilt in F 1 hybrid seedlings of strawberry and concluded that major genes were involved, but there was also a multigenic component, because among susceptible cultivars, the disease severity index varied continuously.…”
mentioning
confidence: 99%